Platelet-Rich Plasma in Female Androgenic Alopecia: A Comprehensive Systematic Review and Meta-Analysis - Zhou, Shuying; Qi, Fei; Gong, Yue; Zhang, Chenxi; Zhao, Siqi; Yang, Xutong; He, Yanling (Frontiers in Pharmacology, 2021)
Introduction: Female pattern hair loss (FPHL) or female androgenic alopecia (AGA) is gradually increasing among young women and may bring serious psychological impacts. Platelet-rich plasma is a novel and promising therapeutic method as a non-surgical treatment for FPHL. Objective: To summarize difference preparation in PRP and treatment regime in FPHL, qualitatively evaluated the current observations, and quantitively analyzed the efficacy of PRP in FPHL treatment. Methods: 6 databases MEDLINE, EMBASE, Web of Science, Cochrane Central Register of Controlled Trials (CENTRAL), LILACS, and CNKI were searched with terms like “platelet-rich plasma” and synonyms for androgenic alopecia (AGA) and female pattern hair loss (FPHL). Meta-analysis was conducted with enrolled observations studies and randomized controlled trials (RCT) separately with the random-effect model. Results: 636 literature and 12 trials from databases were evaluated. A total of 42 studies 1569 cases including 776 female participants covering 16 randomized controlled trials and 26 observational trials were included for qualitative synthesis study and systematic review. PRP showed positive efficacy in the treatment of FPHL in hair density comparing to the control groups with odds ratio [OR] 1.61; 95% CI 0.52-2.70 as well as compared to baseline with OR 1.11; 95% CI 0.86-1.37. Conclusion: PRP showed efficacy in the therapy of FPHL through hair density evaluation. Further studies are needed to define standardized protocols and large-scale randomized trials still need to be conducted to confirm its efficacy.